EVALUASI TINGKAT POLUTAN DARI KEGIATAN PENGELOLAAN SAMPAH DI RUMAH KOMPOS SRIKANA DAN KEPUTRAN KOTA SURABAYA - Irma Nur Asifa; Imam Thohari; Waluyo Jati (Poltekkes Kemenkes Surabaya, 2013)
Garbage materials are able to contaminate the environment in three ways:physically, chemically, and biologically. The large composition of garbage require managementand processing to reduce garbage load entering the TPA. In relation to this, Dinas Kebersihandan Pertamanan Kota 5urabaya has initiated composting of organic wastes partly to reducetheir volume. This study was aimed at measuring pollutants in compost materials especially interms of CO, 502, and H25 parameters. This activity was carried out in Composting Houses of5rikana and Keputran 5urabaya.This descriptive study was performed by measuring CO, SOb and H25 andlaboratory examination. The population under study was composting houses (18 sites) and thesample size was 2 composting houses.Results showed that pollutant level of CO, 502 and H25 in the air was not exceedingthe quality standard being implemented in East Java. The CO level in 5rikana CompostingHouse was 4.21 «(JgjNm3) and in residential area was 3.37 «(JgjNm3). 502 level in compostinghouse was 12.04 «(Jg/Nm3), while outside of house of 16.71 «(JgjNm3) and in residential areawas 4.16 «(Jg/Nm3). The H25 level in composting house was 9.13 «(Jg/Nm3), outside the housewas 6.54«(JgjNm3) and in residential area was 3.22 «(JgjNm3). The CO level in KeputranComposting House was 9.66 «(Jg/Nm3), in outside of the house was 15,74 (uq/Nrn